Thermal performance of planktonic ciliates differs between marine and freshwaters: A case study providing guidance for climate change studies. Issue 6 (28th September 2022) - Lukić, Dunja; Limberger, Romana; Agatha, Sabine; Montagnes, David J. S.; Weisse, Thomas
Abstract: Predicting the performance of aquatic organisms in a future warmer climate depends critically on understanding how current temperature regimes affect the organisms' growth rates. Using a meta‐analysis for the published experimental data, we calculated the activation energy ( E a ) to parameterize the thermal sensitivity of marine and freshwater ciliates, major players in marine and freshwater food webs. We hypothesized that their growth rates increase with temperature but that ciliates dwelling in the immense, thermally stable ocean are closely adapted to their ambient temperature and have lower E a than ciliates living in smaller, thermally more variable freshwater environments. The E a was in the range known from other taxa but significantly lower for marine ciliates (0.390 ± 0.105 eV) than for freshwater ciliates (0.633 ± 0.060 eV), supporting our hypothesis. Accordingly, models aiming to predict the ciliate response to increasing water temperature should apply the environment‐specific activation energies provided in this study.